2016
DOI: 10.7759/cureus.728
|View full text |Cite
|
Sign up to set email alerts
|

Core Measures for Congestive Heart Failure in a Tertiary Care Setting in Pakistan

Abstract: Purpose: Heart failure presents a huge burden for individual patients and the healthcare system as a whole. This study aims to assess the adherence to these core measures as identified by the Joint Commission on Accreditation of Healthcare Organizations (JCAHO)/ American Heart Association (AHA) by physicians of Pakistan.Materials and Methodology: We conducted a cross-sectional study in Shifa International Hospital, Islamabad, Pakistan from the period of April 2013 to April 2016. Patients with a primary diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…It has been reported that 4.5% patients developed heart failure during one week follow-up and 6.3% developed during a six month period. [11][12][13] In GULFRACE study conducted on the Arab Middle East population on the acute heart failure complicating ACS demonstrates 20% heart failure during hospital stay; proportion increased with the age almost 50% above 70 years of age. 14 In this study, 10.6% of NSTE-ACS patients developed HF during their hospital stay.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that 4.5% patients developed heart failure during one week follow-up and 6.3% developed during a six month period. [11][12][13] In GULFRACE study conducted on the Arab Middle East population on the acute heart failure complicating ACS demonstrates 20% heart failure during hospital stay; proportion increased with the age almost 50% above 70 years of age. 14 In this study, 10.6% of NSTE-ACS patients developed HF during their hospital stay.…”
Section: Discussionmentioning
confidence: 99%